FAMILY AND SCHOOL PROTECTIVE FACTORS AS PREDICTORS TO RISK COMPROMISING BEHAVIOURS AMONG SECONDARY SCHOOL STUDENTS IN BAUCHI METROPOLIS - Mustapha, Munir (African Journal of Behavioural and Scale Development Research, 2024)
The study examined the family and school protective factors as predictors to risk-compromising behaviours. Correlational research design was used to determine the relationship between the variables. The population consists of 8,589 students from 22 public secondary schools in Bauchi metropolis and sample of 367 students were selected through the proportionate stratified sampling and simple random sampling techniques. A structured questionnaire titled Protective Factors Questionnaire (PFQ) and Students’ Risk Compromising Behaviours Scale (SRCBS) were used to elicit information from the participants. The finding showed that there is a significant relationship between family protective factors and in school adolescent involvement in risk compromising in Bauchi Metropolis. Also, that weak or poor school discipline is a predictor to in-school adolescent involvement in risk compromising. The study recommends that parents, teachers and community members should organize youth programmes that will focus on fostering known protective factors that are predictors to risks in their environments.